MG-leach: an enhanced leach protocol for wireless sensor network - Hicham Ouldzira; Hajar Lagraini; Ahmed Mouhsen; Mostafa Chhiba; Abdelmoumen Tabyaoui (Institute of Advanced Engineering and Science, 2019)
A wireless sensor network is made up of a large number of small sensor nodes with limited energy resources, which is a real problem for this network. In this article, we will study the ingestion of node energy in these networks at the routing level. In addition, we are modifying one of the most popular routing algorithms for data communication in the WSN: LEACH (Adaptive Hierarchy with Low Power Consumption). The modified version of the LEACH base version